Marketing Mix (4P) Analysis of Javanese Bridal Makeup Services at Anting Wulan Bridal StudioBased on Consumer Perceptions - Devina Permatatika Prabowo; Rina Rachmawati (Universitas Negeri Semarang, 2026)
One of the important parts of the beauty industry in Indonesia is bridal makeup servies, especially traditional Javanese bridal makeup. This makes the competition among makeup studio vendors very tight. In order to survive, companies need to create the right marketing strategy. The study aims to analyze the marketing of Javanese bridal makeup services at the Anting Wulan makeup studio reviewed from the 4P marketing mix which includes products, prices, place, and promotion. The research used a quantitative descriptive method with clients subject who had used Javanese bridal makeup services at the studio. Data was collected through questionnaires as main data on a likert scale and analyzed with descriptive statistics in the form of tables. The results of the study concluded that overall the implementation of marketing strategies was in the very good category with an average score of 89.25. The four aspects in the marketing mix (product, price, place, and promotion) are integrated and contribute significantly to forming positive perceptions and consumer satisfaction.